2018
DOI: 10.1002/art.40490
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Inflammatory Arthritis in Mice by Gut Microbiota Through Mucosal Inflammation and Autoantibody Generation

Abstract: These data support a model in which intestinal dysbiosis triggers mucosal immune responses that stimulate T and B cells that are key for the development of inflammatory arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
127
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(140 citation statements)
references
References 50 publications
12
127
0
1
Order By: Relevance
“…Our data also show that zonulin-dependent increase of intestinal permeability essentially results from microbial dysbiosis initiated by the arthritogenic combination of auto-antigen and adjuvant. This finding is in accordance with a previous study showing that adjuvant alone was not sufficient to initiate mucosal inflammation 39 . In support of the role of microbial dysbiosis, stool transfer was sufficient to initiate intestinal barrier changes in germ-free mice.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our data also show that zonulin-dependent increase of intestinal permeability essentially results from microbial dysbiosis initiated by the arthritogenic combination of auto-antigen and adjuvant. This finding is in accordance with a previous study showing that adjuvant alone was not sufficient to initiate mucosal inflammation 39 . In support of the role of microbial dysbiosis, stool transfer was sufficient to initiate intestinal barrier changes in germ-free mice.…”
Section: Discussionsupporting
confidence: 94%
“…A ltered intestinal microbiota composition, termed "dysbiosis", is associated with autoimmune diseases, particularly type 1 diabetes 1 , multiple sclerosis 2 , systemic lupus erythematosus 3 and rheumatoid arthritis (RA) 4,5 . Several findings support the hypothesis that the onset of RA is linked to the intestinal microbiota, for example that cell wall fragments from various intestinal bacteria have been found to be arthritogenic 6,7 , some drugs used to treat arthritis have antimicrobial effects (chloroquine, sulfasalazine and minocycline) [8][9][10] and the restoration of eubiosis in arthritis patients showing clinical improvement 7,11 .…”
mentioning
confidence: 99%
“…We have also demonstrated that dysbiosis is an early feature of disease in HLA-B27transgenic rats, preceding the onset of clinical disease in the gut or joints (23). Similarly, gut dysbiosis has been demonstrated in RA (24,25), and animal models of RA such as collagen-induced arthritis have been shown to be influenced by the gut microbiome (26,27). In these studies, it is difficult to distinguish the potential effects of the gut microbiome on the disease from the effects of immunologic processes in the intestinal wall or the effects of treatments on the intestinal microbiome.…”
Section: Introductionmentioning
confidence: 54%
“…We have also demonstrated that dysbiosis is an early feature of disease in HLA–B27–transgenic rats, preceding the onset of clinical disease in the gut or joints . Similarly, gut dysbiosis has been demonstrated in RA , and animal models of RA such as collagen‐induced arthritis have been shown to be influenced by the gut microbiome . In these studies, it is difficult to distinguish the potential effects of the gut microbiome on the disease from the effects of immunologic processes in the intestinal wall or the effects of treatments on the intestinal microbiome.…”
Section: Introductionmentioning
confidence: 99%